Comparative Genomic Insights Into the Taxonomic Classification, Diversity, and Secondary Metabolic Potentials of Kitasatospora, a Genus Closely Related to Streptomyces - Li, Yisong; Wang, Meng; Sun, Zhong-Zhi; Xie, Bin-Bin (Frontiers in Microbiology, 2021)
While the genus Streptomyces (family Streptomycetaceae) has been studied as a model for bacterial secondary metabolism and genetics, its close relatives have been less studied. The genus Kitasatospora is the second largest genus in the family Streptomycetaceae. However, its taxonomic position within the family remains under debate and the secondary metabolic potential remains largely unclear. Here, we performed systematic comparative genomic and phylogenomic analyses of Kitasatospora. Firstly, the three genera within the family Streptomycetaceae (Kitasatospora, Streptomyces and Streptacidiphilus) showed common genomic features, including high G+C contents, high secondary metabolic potentials, and high recombination frequencies. Secondly, phylogenomic and comparative genomic analyses revealed phylogenetic distinctions and genome content differences among these three genera, supporting Kitasatospora as a separate genus within the family. Lastly, the pan-genome analysis revealed extensive genetic diversity within the genus Kitasatospora, while functional annotation and genome content comparison suggested genomic differentiation among lineages. This study provided new insights into genomic characteristics of the genus Kitasatospora, and also uncovered its previously underestimated and complex secondary metabolism.